The future BRICS : a synergistic economic alliance or business as usual? - Marino, Rich.; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
The Future BRICS provides in depth quantitative and qualitative questions and answers about the future of the BRICS Forum as a synergistic economic alliance and is a valuable resource for anyone interested in the ongoing international debate about the economic future and sustainability of the emerging markets in general.
Keywords: Science